Chemical constituents and antihistamine activity of Bixa orellana leaf extract. - Yong, Yoke Keong; Zakaria, Zainul Amiruddin; Abdul Kadir, Arifah; Somchit, Muhammad Nazrul; Cheng, Gwendoline Lian Ee; Ahmad, Zuraini (BioMed Central, 2013)

(untitled)
Bixa orellana L. has been traditionally used in Central and South America to treat a number of ailments, including internal inflammation, and in other tropical countries like Malaysia as treatment for gastric ulcers and stomach discomfort. The current study aimed to determine the major chemical constituents of the aqueous extract of B. orellana (AEBO) and to evaluate the antihistamine activity of AEBO during acute inflammation induced in rats.